The Degree to which Kindergarten Teachers in Jordan Possess Scientific and Engineering Practices in Light of the Next Generation Science Standards (NGSS) - Mohammad Khair N. Nawafleh; Amal Fakhari Jaradat (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the degree to which kindergarten teachers in Jordan possess scientific and engineering practices in light of the Next Generation Science Standards (NGSS). Methods: The study used a descriptive survey method. The study tool consisted of a questionnaire of (35) paragraphs spread across eight domains. The study sample consisted of (61) kindergarten teachers in private schools and kindergartens in Bani Ubaid District in Irbid governorate. Results: The results of the study show that the degree to which kindergarten teachers possess scientific and engineering practices was high with a percentage of (79.6%). The results also reveal that there was no statistically significant difference in the degree to which kindergarten teachers in Jordan possess scientific and engineering practices in light of the Next Generation Science Standards (NGSS) due to specialization, educational level, or number of teaching years. Conclusions: The study recommends that schools should provide a science book for public kindergartens in Jordan, as seen in other kindergartens.